2018
DOI: 10.1590/0100-29452018537
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ‘Maxi Gala’ apple trees as affected by budbreak promoters, in São Joaquim-SC

Abstract: The application of rest breaking agents to compensate the lack of chilling is a common practice in apple orchards in Southern Brazil. However, its necessity in areas of greater chilling accumulation has been questioned over the years. The aim of this study was to investigate the performance of 'Maxi Gala' apple in response to different budbreak promoters in São Joaquim, SC.The study was performed in the growing seasons of 2013/2014, 2014/2015, and 2015/2016. Plant material consisted of 10-year-old 'Maxi Gala' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…However, the control treatment always had a longer flowering period. According to Pasa et al [17], the anticipation of flowering with bud break promoters is greater in early applications after completing the dormancy. Bud break promoters shorten the period between full bloom and the end of bloom.…”
Section: Resultsmentioning
confidence: 99%
“…However, the control treatment always had a longer flowering period. According to Pasa et al [17], the anticipation of flowering with bud break promoters is greater in early applications after completing the dormancy. Bud break promoters shorten the period between full bloom and the end of bloom.…”
Section: Resultsmentioning
confidence: 99%
“…Also in apple, Syncron ® + NitroActive ® produced the same effects as hydrogen cyanamide, independently of the weather conditions ( Petri et al, 2016 ). On the contrary, a 3-year study with warm and cold years showed an earlier full bloom in control trees than in trees treated with either Erger ® (2–6%) or hydrogen cyanamide (0.34%) solutions ( Pasa et al, 2018 ). However, it must be said that trees treated with the highest Erger ® concentrations showed higher production levels than the control trees, as previously shown ( Đmrak et al, 2016 ).…”
Section: Effects Of Agrochemicals On Endodormancy Releasementioning
confidence: 94%
“…In recent years, many agrochemical treatments have been performed in warm areas in order to shorten endodormancy and advance flowering time ( Ardiles and Ayala, 2017 ; Rodrigo et al, 2017 ; Ferreira et al, 2019 ). This practice presents significant problems, however, owing to a lack of knowledge about the efficiency of the treatments and the optimal concentrations and application times for distinct species and cultivars ( Ionescu et al, 2017a ; Rodrigo et al, 2017 ; Pasa et al, 2018 ). In order to assist the promotion of endodormancy release in these treatments, other agrochemicals like Armobreak ® or mineral oil have been used to prevent evaporation and help ensure that the treatments penetrate the plant ( Küden et al, 1995 ; Sagredo et al, 2005 ; López Alcolea, 2018 ).…”
Section: Effects Of Agrochemicals On Endodormancy Releasementioning
confidence: 99%
See 2 more Smart Citations